Motivating operations and stimulus control. Issue 1 (18th March 2019) - Edwards, Timothy L.; Lotfizadeh, Amin D.; Poling, Alan
Abstract : The motivating operations concept has generated substantial conceptual analysis and research interest. Following an analysis of how motivating operations affect behavior, one which emphasizes the interactive role of motivating operations and discriminative stimuli, we propose: a) redefining motivating operations as operations that modulate the reinforcing or punishing effectiveness of particular kinds of events and the control of behavior by discriminative stimuli historically relevant to those events, b) dropping the distinction between behavior‐altering and function‐altering effects of motivating operations, and c) reducing or eliminating emphasis on conditioned motivating operations. This reconceptualization of the motivating operations concept is intended to increase its value in predicting and gainfully changing behavior.